Spatial and Sectoral Development of the Region Based on the Development of Agro-Industrial Territorial and Supply Chain Management in Economic Systems - L.E. Krasilnikova (International Journal of Supply Chain Management, 2019)
Abstract. Nowadays there is an urgent need for accelerated development of agricultural industry in Russia. The solution of agro-industrial complex management tasks puts forward the problem of agricultural production reserve growth determination in each of the regions of Russia as one of the most urgent ones. The purpose of the study is to develop evaluation methodology and evaluate agro-industrial territorial-economic systems that have a significant production potential of agricultural sectors in the regions of the Russian Federation. The author justifies the choice of indicators and evaluation criteria. The study was based on economic and mathematical modeling of empirical spatial data, calculated on the basis of official statistical information within the Russian Federation regions. The study made it possible to identify the factors that directly determine the production volumes in agriculture, suggest the use of high quality scenario models to describe this influence, prove that the economics of the regions under review did not reach saturation with agricultural products and there are significant reserves for their further progressive development. The developed scenarios and forecast estimates are effective tools to analyze the development of agricultural sectors, and can also be used as management tools that allow to assess the efficiency of available resource use in agriculture of each of the considered agro-industrial territorial-economic systems. The results of the study have scientific and practical significance. They can be used in research and monitoring of agricultural development in the regions, determining the resource requirements necessary for the development of agricultural industries, the development of sectoral and integrated projects and agriculture development programs.